2003
DOI: 10.1063/1.1587255
|View full text |Cite
|
Sign up to set email alerts
|

Different dynamic and static magnetic anisotropy in thin Permalloy™ films

Abstract: The values of uniaxial anisotropy H k in thin polycrystalline Permalloy™ films measured by static and dynamic methods differ by as much as a factor of 1.5. The anisotropy obtained with a pulsed inductive microwave magnetometer in 2.5 to 100 nm thick Permalloy films exhibits an additional isotropic component of 120 to 240 A/m not observed in static measurements. The static value of anisotropy was obtained with an inductive magnetic hysteresis loop tracer. The time-resolved precessional response was measured as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 7 publications
(7 reference statements)
6
27
0
Order By: Relevance
“…The value obtained is more than twice the value determined from static measurements. This result confirms results obtained by Lopusnik et al, 19 where a rotatable contribution to the anisotropy was observed for sputtered permalloy films.…”
Section: Resultssupporting
confidence: 83%
“…The value obtained is more than twice the value determined from static measurements. This result confirms results obtained by Lopusnik et al, 19 where a rotatable contribution to the anisotropy was observed for sputtered permalloy films.…”
Section: Resultssupporting
confidence: 83%
“…This is in agreement with earlier studies by Lopusnik et al 12 and Schneider et al 13 Fig. 2 as a function of frequency (down triangles).…”
Section: A Small Angle Responsesupporting
confidence: 83%
“…The slight difference between these two FMR frequencies could be due to the difference between static and dynamic magnetic anisotropies of those films, and it has been observed in FeNi film. 37 These high frequency magnetic properties in this study are similar with previous FeGaB films. 22,23 The θ H dependence of the ∆H pp for the three films is shown in Figs.…”
Section: Resultssupporting
confidence: 80%